Characterization of some fungal pathogens causing anthracnose disease on yam in Cross River State, Nigeria - Okon, N.I.; Markson, A.A.A.; Okon, E.I.; Ita, E.E.; Uyoh, E.A.; Ene-Obong, E.O.E.; Ntui, V.O. (2022)
Yam anthracnose is one of the most serious fungal diseases affecting white and water yam production. Screening of available landraces for new sources of durable resistance to the pathogen is a continuous process. In the present study, the pathogens causing anthracnose in Dioscorea alata and Dioscorea rotundata farms in Cross River State yam belt region were characterized. Diseased yam leaves with anthracnose symptoms collected from the farms were used in the isolation, purification and, identification of C. alatae strains using morphological, cultural, and molecular methods. Leaf chlorosis, leaf edge necrosis, blights, dark brown to black leaf spots, shot holes, necrotic vein banding and vein browning were the predominantly observed symptoms. Seven isolates of C. alatae, Ca5, Ca14, Ca16, Ca22, Ca24, Ca32 and Ca34, and one isolate of Lasidioplodia theobromae, Lt1 were found to be associated with yam infection in Cross River State, with Lt1 as the most prevalent, occurring in all the locations. These isolates were classified into four forms which included the slow-growing grey (SGG), the fast-growing grey (FGG), the fast-growing salmon (FGS), and the fast-growing olive (FGO). Sequence analysis of the ITS region revealed <80% nucleotide identity between the isolates and the reference C. gloeosporioides. Pathogenicity test showed that all the isolates displayed typical symptoms of anthracnose disease as were observed in the field, but Lt1 was the most virulent. Inoculation of 20 D. alata and 13 D. rotundata landraces with isolate Lt1, showed that 63.64% of the landraces were susceptible while 36.36%were resistant. D. alata landraces were the most susceptible. This study revealed that anthracnose is prevalent and may assume an epidemic dimension in the yam growing communities of the state. There is need for increased effort in the breeding of yam for anthracnose resistance.